Financial loss estimation of bovine fasciolosis in slaughtered cattle in South Africa. Issue 4 (November 2017) - Jaja, Ishmael Festus; Mushonga, Borden; Green, Ezekiel; Muchenje, Voster
Abstract: South Africa's livestock population is rapidly evolving and consequently will require sustained epidemiological surveillance to detect and prevent diseases which contribute to a decrease in livestock productivity, public health risk and food wastage. Fasciola infection is one of the commonest diseases affecting livestock health and a significant portion of meat and offal's are declared unfit for human consumption. This study assessed the prevalence and monetary losses associated with Fasciola infection at three abattoirs in Eastern Cape Province. A retrospective data of all slaughtered cattle were obtained from Department of Rural Development and Agrarian Reform (DRDAR) from 2010–2012. A prospective abattoir survey was conducted between July 2013 and June 2014 to determine the prevalence and financial loss due to fasciolosis. The highest prevalence was in December and January (23%) while the lowest prevalence was recorded in May and June (5%). Annual prevalence of Fasciola at abattoirs AB1, were (3.2%, 2.2% and 2.0%), AB2 (6.4%, 4.6% and 3.5%), AB3 (14.4%, 6.9% and 9.5%) for year 2010, 2011 and 2012 respectively. The total financial loss due to Fasciola infection during the active survey of the three abattoirs was ZAR 44, 930 (3456.2 USD). A breakdown of this figure shows that whole liver condemnation was ZAR 25, 230 (2, 357 USD), and partial liver condemnation was ZAR 19, 700 (1515.4 USD). The present study reveals the economic loss due to liver condemnation from Fasciola infection and provides regional baseline information regarding the prevalence of Fasciola in cattle at three abattoirs.